O-L09 Determining the Prognostic Utility of Immuno-histochemically detected Trans-membranous Human Equilibriative Nucleoside Transporter 1 (hENT1) in Patients Undergoing Hilar Cholangiocarcinoma Resection. (16th December 2021) - Bird, Nicholas; Manu, Nichola; QuinnL, Mark; Diaz-Nieto, Rafa; Fenwick, Stephen; Jones, Robert; Malik, Hassan
Abstract: Background: Human equilibriative nucleoside transporter protein 1 (hENT1) is a trans-membranous protein which facilitates nucleoside transport in to the cell. Immunohistochemically-detected hENT1 abundance is increased in cholangiocarcinoma tumour cells compared to matched non-tumour cells and increased in highly metabolising cells. The privately-held Mackey 10D7G2 hybridoma has demonstrated prognostic utility in Pancreatic Ductal Adenocarcinoma patients. The commercially available Proteintech Polyclonal hENT1 antibody's prognostic utility has not been previously assessed. Cellular Ki67 expression has been linked to mitotic indices of tumour proliferation. This proof-of-concept study aims to assess the antibodies prognostic utility for hilar cholangiocarcinoma patients undergoing surgical resection. Methods: Between February 2009 and February 2016 54 patients underwent resection for peri-hilar cholangiocarcinoma. Formalin-Fixed Paraffin Embedded (FFPE) blocks from a sub-set of 44 resected specimens were retrieved. Appropriate areas of tumour were sampled from the blocks and a Tissue-Matched Array (TMA) was constructed. The TMA underwent staining for each antibody. H-scores were utilised to determine intensity of expression. Correlation of expression between antibodies was determined by Pearson correlation co-efficient and Chi-squared where appropriate. Silencing RNA transfected HepG2 cell-lines was used to determine hENT1 staining by the Proteintech antibody. Demographic and survival characteristics for the patients were acquired from a prospectively held database linked to Hospital Episode Statistics. Survival characteristics were calculated with global log-rank calculations. Results: There was significant correlation between the Mackey 10D7G2 and the Proteintech antibodies (p < 0.001). There was significant correlation between the Proteintech hENT1 antibody expression and Ki67 expression (p = 0.02). Knockdown of hENT1 with silencing RNA transfected HepG2 cells was confirmed by Western blot in a time-dependent fashion over 72 hours. The antibodies (Mackey; Proteintech; Ki67) did not achieve significance for predicting OS (p = 0.75; 0.63; 0.22 respectively). Nodal stage (p = 0.03) and grade of tumour differentiation (p = 0.02) were the univariate tumour variables with prognostic utility. Conclusions: While the Proteintech antibody demonstrates concordance with the 10D7G2 antibody in determining hENT1 expression the antibodies did not demonstrate significant prognostic ability in this proof-of-concept study. Standard histopathological co-variates retain prognostic utility within the cohort.